Tribological property investigation on a novel pneumatic actuator with integrated piezo actuators. (June 2015) - Gao, Han; de Volder, Michaël; Cheng, Tinghai; Bao, Gang; Al-Bender, Farid; Reynaerts, Dominiek
Abstract: Pneumatic piston–cylinder actuators are commonly used in industry for a variety of automation and robotics applications. In order to suppress leakage, these actuators comprise seal rings which unfortunately introduce friction and affect the positioning accuracy and output force. This article investigates vibrations of the seal generated by integrated piezo actuators to reduce friction force. For this, two piezoelectric stacks are integrated in the cylinder and used to excite vibration modes. This concept was studied in a compact cylinder pneumatic actuator with a bore diameter of 5 mm and a stroke of 10 mm. Dry friction measurement shows a 52% reduction from the original friction force at a driving frequency of 18.29 kHz and vibration amplitude of 0.05 μm. In the wet friction experiments, the friction force can be reduced by 54% from the original wet friction with vibrations at amplitude of 0.04 μm. Highlights: We fabricate a novel pneumatic actuator with integrated piezo actuators for the tribological property investigation. We measure the dry and wet friction with vibrations on the pneumatic actuator. Dry friction with ultrasonic vibration shows a 52% reduction from the original friction. Wet friction experiment shows a 54% reduction from the original friction.